Impact of Antimicrobial Prophylaxis for Severe Acute Pancreatitis on the Development of Invasive Candidiasis: A Large Retrospective Multicenter Cohort Study. Issue 4 (April 2019) - Horibe, Masayasu; Sanui, Masamitsu; Sasaki, Mitsuhito; Honda, Hitoshi; Ogura, Yuki; Namiki, Shin; Sawano, Hirotaka; Goto, Takashi; Ikeura, Tsukasa; Takeda, Tsuyoshi; Oda, Takuya; Yasuda, Hideto; et al.
Abstract : Objective: Antimicrobial prophylaxis is not generally recommended for patients with severe acute pancreatitis (SAP) owing to the limited clinical benefits. Nonetheless, it is frequently administered in actual practice given the patients' critical condition and the lack of solid evidence showing adverse effects of antimicrobial prophylaxis. We evaluated herein an association between antimicrobial prophylaxis and invasive pancreatic candidiasis as an adverse effect in patients with SAP. Methods: This is a retrospective cohort study of all consecutive patients with SAP who were admitted to the study institutions (n = 44) between January 1, 2009, and December 31, 2013. We performed multivariable logistic regression analysis adjusting for the extent of pancreatic necrosis and surgical interventions for invasive pancreatic candidiasis. Results: Of the 1097 patients with SAP, 850 (77.5%) received antimicrobial prophylaxis, and 21 (1.9%) had invasive pancreatic candidiasis. In multivariable logistic regression analysis, antimicrobial prophylaxis was significantly associated with the development of invasive pancreatic candidiasis (adjusted odds ratio, 4.23; 95% confidence interval, 1.14–27.6) ( P = 0.029). Conclusions: The results suggest that antimicrobial prophylaxis may contribute to the development of invasive pancreatic candidiasis, and therefore, the routine use of antimicrobial prophylaxis for SAP may be discouraged.